2016
DOI: 10.4314/mcd.v11i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Value of useful goods and ecosystem services from Agnalavelo sacred forest and their relationships with forest conservation

Abstract: Agnalavelo forest provides necessary natural resources to people who live in its surroundings (Communities of Mahaboboka, Amboronabo and Mikoboka in southwestern Madagascar). The aim of this study is to document goods and ecosystem services provided by Agnalavelo forest to local people and to use it as a tool for the identification of priorities for forest conservation. Oral interviews were undertaken from 2010-2013 with local communities living in the vicinity of Agnalavelo forest. This study also investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…In this area, the sub-humid forest of Analavelona is an exception where 403 plant species grouped in 100 families were inventoried and 73% of them are endemic to Madagascar [ 20 ]. Villagers surrounding Analavelona forest and even spirit healer from far away have traditional rights to access to medicinal and magical plants species from the sacred forest following local rules [ 21 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…In this area, the sub-humid forest of Analavelona is an exception where 403 plant species grouped in 100 families were inventoried and 73% of them are endemic to Madagascar [ 20 ]. Villagers surrounding Analavelona forest and even spirit healer from far away have traditional rights to access to medicinal and magical plants species from the sacred forest following local rules [ 21 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…The Alandraza-Agnalavelo sacred forest was recently classified as a critically threatened Critically threatened ecosystem [ 74 ]. We previously showed the forest provides 3 types of services to people at local, regional, and national levels, including ecologic, cultural and provisioning services [ 17 ]. This study adds the vitally important service of providing nutritious food to local communities in vulnerable periods of the year.…”
Section: Discussionmentioning
confidence: 99%
“…Wild food consumption in Madagascar has been studied in relation to both biodiversity losses [ 15 ] and human nutrition [ 16 ]. We previously conducted research in the Agnalavelo forest that showed people seek out 40 wild edible plant species for consumption to mitigate hunger during drought periods, forming the basis of the present study [ 17 ]. This study aimed to examine the association of wild plant and animal species consumption during the hunger season with diet diversity and child growth near the Alandraza-Agnalavelo protected forest in Southwestern Madagascar.…”
Section: Introductionmentioning
confidence: 99%
“…Celtis africana: Used to treat rheumatism (Yineger et al 2008). Celtis africana and Celtis gomphophylla, are used as raw material for medicines in Madagascar, especially for diarrhea and digestive system problems (Randrianarivony et al 2016(Randrianarivony et al , 2017. Celtis australis: Used as blood purifier and tonic (Muhammad et al 2019), as well as against allergies (Ur-Rahman et al 2018).…”
Section: Local Medicinal Usesmentioning
confidence: 99%